Comparative Enhancement of Motor Function and BDNF Expression Following Different Brain Stimulation Approaches in an Animal Model of Ischemic Stroke. (October 2020) - Sims, Serena-Kaye Kinley-Cooper; Rizzo, Aitana; Howard, Kern; Farrand, Ariana; Boger, Heather; Adkins, DeAnna L.
Background: Combinatory intervention such as high-frequency (50-100 Hz) excitatory cortical stimulation (ECS) given concurrently with motor rehabilitative training (RT) improves forelimb function, except in severely impaired animals after stroke. Clinical studies suggest that low-frequency (≤1 Hz) inhibitory cortical stimulation (ICS) may provide an alternative approach to enhance recovery. Currently, the molecular mediators of CS-induced behavioral effects are unknown. Brain-derived neurotrophic factor (BDNF) has been associated with improved recovery and neural remodeling after stroke and thus may be involved in CS-induced behavioral recovery. Objective: To investigate whether inhibitory stimulation during RT improves functional recovery of severely impaired rats, following focal cortical ischemia and if this recovery alters BDNF expression (study 1) and depends on BDNF binding to TrkB receptors (study 2). Methods: Rats underwent ECS + RT, ICS + RT, or noCS + RT treatment daily for 3 weeks following a unilateral ischemic lesion to the motor cortex. Electrode placement for stimulation was either placed ipsilateral (ECS) or contralateral (ICS) to the lesion. After treatment, BDNF expression was measured in cortical tissue samples (study 1). In study 2, the TrkB inhibitor, ANA-12, was injected prior to treatment daily for 21 days. Results: ICS + RT treatment significantly improved impaired forelimb recovery compared with ECS + RT and noCS + RT treatment. Conclusion: ICS given concurrently with rehabilitation improves motor recovery in severely impaired animals, and alters cortical BDNF expression; nevertheless, ICS-mediated improvements are not dependent on BDNF binding to TrkB. Conversely, inhibition of TrkB receptors does disrupt motor recovery in ECS + RT treated animals.